The Sussex Oxford Compassion for the Self Scale validity in a working sample using classical test theory, item response theory and network analysis - Meng, Hongxing; Wang, Xiaozhuang; Liu, Hongpei (Frontiers in Psychology, 2023)
Self-compassion is a relatively new construct in the scientific literature. and there is currently a lack of robust psychometric measures of self-compassion in the workplace. Therefore, validating the Sussex Oxford Compassion for the Self Scale (SOCS-S) in various cultural settings is essential to add to the existing research on the psychometric properties of the scale. This study aimed to evaluate the validity of the SOCS-S in a Chinese working sample of 1132 participants (39.4% males) using Classical Test Theory (CTT), Item Response Theory (IRT), and Network Analysis. The results supported the validity of the SOCS-S’s five-factor structure, with high internal consistency and measurement invariance across genders. IRT was applied using a graded response model to assess the overall SOCS-S scale items, indicating that all 20 items had sufficient discrimination indices and acceptable difficulty indices. Moreover, it is worth noting that the results of the network analysis are consistent with those of the IRT analysis. In summary, the study confirms the validity of the SOCS-S as a scale for assessing self-compassion among Chinese occupational groups.